Molecular identification of pfcytb, pfdhfr, and pvmrp1 mutations in imported malaria cases in Chile - Oyarce, Alan; Huaccha, Lizbeth; Cordero, Esteban M.; Parra, Bárbara; Fernández, Jorge; Soto-Marchant, Mario E.; Santis-Alay, Natalia T.; Jercic, María Isabel (Frontiers in Malaria, 2025)
A key challenge in the global effort to combat malaria is the emergence of drug resistance. Malaria-free countries must also address issues such as limited access to antimalarial drugs and treatment failures caused by drug resistance. Chile, as a malaria-free country, faces the risk of malaria being reintroduced due to the presence of the malaria vector in its continental territory. This study aims to analyze the genetic profile associated with antimalarial drug resistance in the pfcytb, pfdhfr, and pvmrp1 genes. A total of ninety blood samples from 55 individuals who had been diagnosed with malaria in Chile between 2019 and 2021 were subjected to mutational analysis. The parasites target genes were amplified by polymerase chain reaction (PCR) out of total DNA extracted from patient blood samples and the amplicons submitted to DNA sequencing. All the genes analyzed had at least one mutation. In the pfdhfr gene, three mutations were observed (S108N/N51I/C59R). In the pfcytb gene, the Y268C mutation, found in post-treatment samples, was associated with treatment failure. In the pvmrp1 gene, five distinct mutations were identified. Of these, the Y1393D (100%) and V1478I (95.2%) were the most common. Our findings indicate that both P. falciparum and P. vivax samples from travelers and migrants in Chile carry mutations in genes linked to malaria resistance. The circulation of parasites with potential drug resistance in non-endemic countries further complicates the challenge of ensuring adequate treatment. It is crucial to continue genetic surveillance and expand the search for new resistance markers for Plasmodium species.